A Training on Ecobrick Making at the Community Information and Counseling Center for Youth Bukit Gado-Gado Padang - Suci Fajrina; Lufri Lufri; Ria Anggriyani (Pelita Eksakta, 2023)
Training the community to process plastic waste using ecobrick techniques can be useful and one of the keys to the success of a plastic waste recycling program. Gado-Gado Hill is one of the sub-districts in Padang, which has now become a magnet for tourists who want to see the natural beauty of Padang from above. As a tourist destination, this area has the potential to experience environmental damage due to plastic waste if the community is unable to manage plastic waste properly. In Bukit Gado-Gado Village, there is a community called the Bukit Gado-Gado Youth Information and Counseling Center. This community has a challenge, namely the lack of volunteers to develop the creativity of teenagers and children. The aim of this community partnership program is to provide training to community members in efforts to deal with plastic waste using ecobrick techniques. The long-term goal of this program is independence for community members in the economic sector as a new business opportunity to create a product with high marketability.